A microanalysis of musical interactions in music therapy : clinical improvisations of an adult with visual impairment - Avila, Clariane Liz (2018)
To date, published studies involving music therapy (MT) and clients with visual impairment (VI) are few. Adults with VI who experience MT are a less studied group, despite comprising majority of the visually-impaired population. The aim of this study was to investigate how significant musical interactions occur and change throughout the process of therapy in the form of a microanalytic case study of clinical improvisations between an adult client with degenerative VI and his music therapist. Results suggest that music improvisation involving musical interactions such as singing, humming, and shared playing of instruments (together or in turns) led to fruitful ways of working with an adult client with VI. Additionally, observing aspects of being in the musical space together and how the client and therapist musick the sounds, silences, and other emergent improvisational motifs provide insight to the way the relational or interactional dynamics change over time from dependent playing to musical partnership and independence.